Radiative cooling: Fundamental physics, atmospheric influences, materials and structural engineering, applications and beyond. (February 2021) - Lin, Keng-Te; Han, Jihong; Li, Ke; Guo, Chunsheng; Lin, Han; Jia, Baohua
Abstract: This review article aims to provide a comprehensive understanding of radiative cooling technology and their applications, especially on the integration of radiative coolers with devices. Over the past decades, radiative coolers and their applications have been intensively investigated because of their outstanding features for energy saving. The fundamental mechanism and characteristics of radiative cooling, in particular, atmospheric influences, and photothermal manipulation through structural and materials engineering, play essential roles in most of the practical applications. In general, these main factors concomitantly influence the cooling performance of a radiative cooler. However, comprehensive review investigating these main parameters simultaneously remains elusive. In this article, the fundamental features of radiative coolers are discussed, especially the influences of atmospheric conditions at different locations on the radiative coolers, and the photothermal manipulation capability and cooling performance of different types of radiative coolers. The applications, challenges faced in this field and the future trends are also discussed. This article will provide guidance towards integration of radiative coolers with functional devices for both academic researchers and engineers in the fields of energy harvesting, fluidic cooling, energy efficient clothing, and architecture. Graphical Abstract: ga1 Highlights: The article provides a timely and comprehensive understanding of radiative cooling technology and their applications. The fundamental features and cooling performances of radiative coolers are elucidated and discussed. The applications, challenges faced in the field of radiative cooling technology and the future trends are elucidated. This article provides guidance towards integration of radiative coolers with functional devices.